2005
DOI: 10.2106/jbjs.d.02904
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Quality of Cartilage Repair Studies

Abstract: Therapeutic Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
189
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(201 citation statements)
references
References 66 publications
9
189
3
Order By: Relevance
“…Coleman [6] reported major methodological deficiencies in studies reporting surgical outcome for patellar tendinopathy. Similar low-methodological qualities were identified by Jakobsen et al [11] and Tallon et al [16] for surgical outcome studies on cartilage repair and Achilles tendinopathy, respectively. Hence, we conducted this study to analyse the quality of all the studies which have reported outcome following cemented totaljoint arthroplasty of the thumb and have suggested few recommendations to minimise this problem.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Coleman [6] reported major methodological deficiencies in studies reporting surgical outcome for patellar tendinopathy. Similar low-methodological qualities were identified by Jakobsen et al [11] and Tallon et al [16] for surgical outcome studies on cartilage repair and Achilles tendinopathy, respectively. Hence, we conducted this study to analyse the quality of all the studies which have reported outcome following cemented totaljoint arthroplasty of the thumb and have suggested few recommendations to minimise this problem.…”
Section: Introductionsupporting
confidence: 68%
“…However, there have been no analyses about the quality of these outcome studies. Methodological deficiencies have been reported in articles reporting surgical outcome for various other conditions [6,11,16]. Coleman [6] reported major methodological deficiencies in studies reporting surgical outcome for patellar tendinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of cartilage repair, which is a key target for regenerative medicine, several cell-based repair strategies already exist, including implantation of cultureexpanded articular chondrocytes, implantation of culture-expanded MSCs, and bone microfracture techniques, among other strategies (14,24,25). Admittedly, the desired outcome of cartilage repair has been inconsistent, and sometimes only modest results have been achieved, but investigators in the field recognize that factors other than the cells themselves, including growth factors, tissue scaffolds, the diseased microenvironment (26), and alignment of the joint (27), may have a crucial influence on the outcome (Table 2). Therefore, regardless of the source of the stem cell, these factors will have to be understood to maximize the benefits of stem cell therapy.…”
Section: Existing Msc-based Cartilage and Bone Therapiesmentioning
confidence: 99%
“…Indeed, cells with analogous biologic features have been isolated from other tissues, including synovial membrane (26,73), synovial fluid (33), periosteum (74,75), trabecular bone (76), and adipose tissue (77). Regardless of their source, MSCs possess multipotency and appear to have distinctive features in vitro and in vivo.…”
Section: Development Of Novel Therapies Based On Msc Tissue Specificimentioning
confidence: 99%
“…Abrasion arthroplasty, subchondral drilling, autologous osteochondral grafts, periosteal-perichondral grafts, chon-drocyte transplantation and gene therapy have been developed for the treatment of focal chondral lesions with acceptable results [1,7,12,19,22]. Successful long-term clinical results are obtained with the use of an autologous osteochondral cylindrical graft for the repair of osteochondral defects [5,11,18].…”
Section: Introductionmentioning
confidence: 99%